Walk 1 BEGINNING - -, - (project baikal, 2011)
Monument to the Founders of Irkutsk “…There Is No Other Place to Raise the Fortress in…” About the Prehistory of Irkutsk Ostrog The Irkutsk Church of Our Savior: Application of Innovative Technologies When Working out the Restoration Project and Earthquake Protection The Saints Peter and Fevronia of Murom Bank Protection and Improvement of the Embankment of Angara River in Irkutsk The Office Building and the Hostel Complex for Teachers Training Institute on CES Embankment Academy of Law (Nekrasov Street 4-6, Irkutsk) The CPSU City Committee and the City Executive Committee Office Building Kazan Cathedral